CLINICAL PATHOLOGICAL CHARACTERISTICS OF SYSTEMIC LUPUS ERYTHEMATOSUS PATIENTS PRESENTING AT A TERTIARY CARE HOSPITAL - A SINGLE CENTRE STUDY: Clinical Characteristics of SLE Patients - Shiram, Dr Syed Ali; Ahmed, Mushtaq; Nisar, Shazia (Pakistan Armed Forces Medical Journal, 2018)
Objective: To determine the frequency of clinopathological characteristics of systemic lupus erythematosus (SLE) patients presenting to Military Hospital (MH) Rawalpindi. Study Design: Descriptive cross sectional study. Place and Duration of Study: The study was carried out at MH Rawalpindi, from Jan 2011 to Dec 2013. Material and Methods: All patients presenting to Rheumatology department, MH Rawalpindi with a diagnosis of SLE were included in this study. Presenting features, clinical profile and laboratory parameters of patients were recorded. Results: A total of 76 patients were included in this study, 70 (92.1%) were females and 6 (7.9%) male patients with female- male ratio of 11.6:1. Mean age at presentation was 33 ± 8.31 years. Seventy two patients (94.7%) were anti nuclear antibody (ANA) positive, 63 (83%) were positive for anti-double stranded deoxyribonucleic acid (anti-dsDNA) antibody and 6 (7.9%) were anti Smith positive. Seventy (92.1%) patients had musculoskeletal symptoms, 65 patients (85.5%) had fever, 36 (47.4%) patients had cutaneous symptoms, and 20 patients (26.3%) had oral ulcers. About 13 patients (17.1%) had alopecia and 15 patients (19.7%) had serositis. Forty two patients (55.3%) had nephritis, 20 patients (26.3%) had lupus cerebritis, 57 patients (75%) had hematological involvement, 9 patients (11.83%) had pulmonary involvement, 8 patients (10.5%) had rheumatoid arthritis (RA) factor positive and 7 patients (9.2%) had overlap syndrome. Conclusion: Renal and hematological involvement was more common in this study population while mucocutaneous features and neuropsychiatric features were comparable to many local studies with exception to that of Lahore based study that showed much higher percentage of these features. These results reflect the need to have a high index of suspicion for kidney and hematological involvement in SLE patients.